The Ralstonia solanacearum Type III Effector RipAY Is Phosphorylated in Plant Cells to Modulate Its Enzymatic Activity - Wei, Yali; Sang, Yuying; Macho, Alberto P. (Frontiers in Plant Science, 2017)
Most bacterial pathogens subvert plant cellular functions using effector proteins delivered inside plant cells. In the plant pathogen Ralstonia solanacearum, several of these effectors contain domains with predicted enzymatic activities, including acetyltransferases, phosphatases, and proteases, among others. How these enzymatic activities get activated inside plant cells, but not in the bacterial cell, remains unknown in most cases. In this work, we found that the R. solanacearum effector RipAY is phosphorylated in plant cells. One phosphorylated serine residue, S131, is required for the reported gamma-glutamyl cyclotransferase activity of RipAY, responsible for the degradation of gamma-glutamyl compounds (such as glutathione) inside host cells. Accordingly, non-phosphorylable mutants in S131 abolish RipAY-mediated degradation of glutathione in plant cells and the subsequent suppression of plant immune responses. In this article, we examine our results in relation to the recent reports on the biochemical activities of RipAY, and discuss the potential implications of phosphorylation in plant cells as a mechanism to modulate the enzymatic activity of RipAY.